The effect of introversion and Extroverts of individuals in the socialization of public space - Yadegari, Zohre; Alinaghi, Behnoud (Technium Social Sciences Journal, 2020)
Urban architects and designers have been trying to create life in the public space for many years. One way to make space dynamic is to consider socialization. Public space requires socialization and require people to be present in the environment. This study identifies the way to socialization by creating a sense of belonging in space, by exploring a sense of belonging in space; he improve the quality of public space. It expresses a sense of belonging to individual needs such as introverted and extroverted traits. This research starts its work by basic question that they are looking in public space. The purpose of this study is to investigate the concepts of introversion and extroversion as factors affecting the quality of public space. After reviewing these studies, criteria and principles for the socialization of public spaces are outlined. The results of the authors’ studies showed that to create a space for personality needs, one should have space with approaches such as: Space for energy depletion, space, diversity in the environment and high quality of space for long-term use. Space tranquility for group activities are also essential. And for designers who value the perpetuation of identity and, these components offer design solutions.